Dietary anthocyanins as a complementary medicinal approach for management of inflammatory bowel disease. (July 2014) - Sodagari, Hamid Reza; Farzaei, Mohammad Hosein; Bahramsoltani, Roodabeh; Abdolghaffari, Amir Hossein; Mahmoudi, Maryam; Rezaei, Nima
<x xml:space="preserve">Abstract</x> Inflammatory bowel disease (IBD) is thought to result from a chronic or relapsing activation of the immune system in the GI tract. A growing body of evidence confirms the health benefits of dietary anthocyanins as plant-derived natural agents. The aim of this review is to provide an overview of several natural products rich in anthocyanins used worldwide for the treatment of IBD. Anthocyanins possess both protective and therapeutic functions in the management of IBD by alleviating oxidative stress processes, cytoprotective functions, downregulation of inflammatory cytokines and suppressing cellular signaling pathways of inflammatory processes. In conclusion, the consumption of anthocyanin-rich natural formulations must be promoted on the basis of their possible function in the prevention and treatment of gastrointestinal inflammatory disorders.